2020
DOI: 10.5212/olharprofr.v.23.15840.
|View full text |Cite
|
Sign up to set email alerts
|

Análises De Pesquisas Sobre a Educação Especial Inclusiva: A (In)diferenciação E O Preconceito

Abstract: O artigo apresenta as análises das publicações que relatam investigações empíricas de três grupos brasileiros referências para a Educação Especial Inclusiva: o Laboratório de estudos sobre o Preconceito, o Observatório Nacional de Educação Especial e o Laboratório de Estudos e Pesquisas em Ensino e Diferença. O percurso teórico-metodológico contou com a pesquisa documental bibliográfica para a seleção dos artigos e as análises apoiam-se na Teoria Crítica da Sociedade e em autores do marco temático da Educação … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In order to be able to share vigilance in care, the participants of this study used the construction of a support network in the school as a strategy, thus creating co-responsibility for care. One review concluded that teachers perceive themselves as powerless in the face of insecurity and unprepared in carrying out an efficient teaching plan to attend to students with special health needs (Salgado & Silva, 2020). Other studies have shown that mothers, recognizing the unpreparedness of these professionals, seek to ensure adequate care planning in the school context, sharing information and teaching about the illness and subsequent treatment of their children (Kingod & Grabowski, 2020;Nieto-Eugenio et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In order to be able to share vigilance in care, the participants of this study used the construction of a support network in the school as a strategy, thus creating co-responsibility for care. One review concluded that teachers perceive themselves as powerless in the face of insecurity and unprepared in carrying out an efficient teaching plan to attend to students with special health needs (Salgado & Silva, 2020). Other studies have shown that mothers, recognizing the unpreparedness of these professionals, seek to ensure adequate care planning in the school context, sharing information and teaching about the illness and subsequent treatment of their children (Kingod & Grabowski, 2020;Nieto-Eugenio et al, 2020).…”
Section: Discussionmentioning
confidence: 99%